Innovative geopolymer‑based cold asphalt emulsion mixture as eco‑friendly material - Anmar, Dulaimi; Al Busaltan, Shakir; Md Azree, Othuman Mydin; Lu, Dong; Onuralp Özkılıç, Yasin; Putra Jaya, Ramadhansyah; Arman, Ameen (Nature Publishing Group, 2023)
In recent years, there has been a growing interest in cold asphalt emulsion mixture (CAEM) due to its numerous advantages, including reduced CO2 emissions, energy savings, and improved safety during construction and application. However, CAEM has often been considered inferior to hot mix asphalt (HMA) in terms of performance. To address this issue and achieve desirable performance characteristics, researchers have been exploring the modification of CAEM using high-cost additives like ordinary Portland cement. In this study, the focus was on investigating the effects of utilizing waste alkaline Ca(OH)2 solution, ground granulated blast-furnace slag (GGBFS), and calcium carbide residue (CCR) as modifiers to enhance the properties of CAEM. The aim was to develop an innovative geopolymer geopolymer-based cold asphalt emulsion mixture (GCAE). The results of the study revealed that the use of waste alkaline Ca(OH)2 solution led to an increase in early hydration, which was confirmed through scanning electron microscopy. Furthermore, the experimental findings demonstrated that waste alkaline Ca(OH)2 solution significantly contributed to the rapid development of early-age strength in GCAE. As a result, GCAE showed great potential for utilization in pavement applications, particularly for roads subjected to harsh service conditions involving moisture and temperature. By exploring these alternative modifiers, the study highlights a promising avenue for enhancing the performance of CAEM and potentially reducing the reliance on expensive additives like ordinary Portland cement. The development of GCAE has the potential to offer improved performance and durability in pavement applications, thus contributing to sustainable and efficient road infrastructure.